Bountiful deserts : sustaining Indigenous worlds in northern New Spain - Radding Murrieta, Cynthia (Latin American landscapes., 2022)
"Set in the arid lands of northwestern Mexico, this book foregrounds the knowledge of Indigenous peoples who made the land bountiful in their material resources and sacred spaces. It uses the tools of history, anthropology, geography, and ecology to recreate the means of defending Indigenous worlds through colonial encounters, the formation of mixed societies, and direct conflicts over forests, grasslands, streams, and coastal estuaries that sustained wildlife, horticulture, foraging, hunting, fishing, and - after European contact - livestock and extractive industries. It returns in each chapter to the spiritual power of nature and the enduring cultural significance of the worlds that Indigenous communities created and defended"--